2022
DOI: 10.3390/brainsci12020184
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Prominent Cortical Vessels on Susceptibility-Weighted Imaging in Acute Ischemic Stroke Patients Treated with Recanalization Therapy

Abstract: Prominent cortical vessels on susceptibility-weighted imaging (PCV–SWI) correlate with poor leptomeningeal collaterals. However, little is known about PCV–SWI in recanalization therapy-treated patients with anterior circulation large vessel occlusions (LVO). We investigated PCV–SWI-based assessment of leptomeningeal collaterals and outcome predictions in 100 such patients in an observational study. We assessed PCV–SWI using the Alberta Stroke Program Early CT Score and evaluated leptomeningeal collaterals on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A total of 7 studies were prospective in design, while 13 studies were retrospective. A total of 16 studies involving 1,488 patients ( 8 , 10 , 12 14 , 16 – 21 , 23 – 27 ) were pooled for an assessment of functional outcome, in which 13 studies involving 1,347 patients had this reported at 90 days ( 10 , 12 , 13 , 16 – 21 , 23 , 25 – 27 ). Four studies ( n = 324) ( 10 , 12 , 19 , 20 ) were performed on recanalization therapy, three ( 10 , 19 , 20 ) of which were intravenous thrombolysis (IVT), and one ( 12 ) of which combined endovascular treatment (EVT) with IVT.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 7 studies were prospective in design, while 13 studies were retrospective. A total of 16 studies involving 1,488 patients ( 8 , 10 , 12 14 , 16 – 21 , 23 – 27 ) were pooled for an assessment of functional outcome, in which 13 studies involving 1,347 patients had this reported at 90 days ( 10 , 12 , 13 , 16 – 21 , 23 , 25 – 27 ). Four studies ( n = 324) ( 10 , 12 , 19 , 20 ) were performed on recanalization therapy, three ( 10 , 19 , 20 ) of which were intravenous thrombolysis (IVT), and one ( 12 ) of which combined endovascular treatment (EVT) with IVT.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 studies involving 1,488 patients ( 8 , 10 , 12 14 , 16 – 21 , 23 – 27 ) were pooled for an assessment of functional outcome, in which 13 studies involving 1,347 patients had this reported at 90 days ( 10 , 12 , 13 , 16 – 21 , 23 , 25 – 27 ). Four studies ( n = 324) ( 10 , 12 , 19 , 20 ) were performed on recanalization therapy, three ( 10 , 19 , 20 ) of which were intravenous thrombolysis (IVT), and one ( 12 ) of which combined endovascular treatment (EVT) with IVT. Five studies ( n = 951) reported END ( 9 , 11 , 13 , 15 , 22 ), while six studies ( n = 352) reported the risk of HT ( 8 , 10 , 20 , 24 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations